Evolução cariotípica e composição da heterocromatina em espécies da subtribo Pleurothallidinae Lindl. (Orchidaceae A.Juss.) - Silva, José Lourivaldo da (2021)
The subtribe Pleurothallidinae is a monophyletic group belonging to the Orchidaceae family, comprising 5,114 species and 44 genera, widely distributed mainly in the neotropical regions. In this study, we aimed to investigate the karyotypic evolution, quantity, and distribution of heterochromatic bands in species of the subtribe Pleurothallidinae. Therefore, nine genera and 26 representatives of the subtribe Pleurothallidinae were analyzed using the CMA/DAPI staining technique, with the purpose of expanding the number of genera and species studied with this method. We sought to answer the following questions: 1) Does the variation in chromosomal numbers and CMA/DAPI band patterns in Pleurothallidinae support the segregation of rec ently proposed genera based on molecular phylogeny? 2) Is the quantity and distribution of CMA/DAPI bands uniform in these genera? 3) Can Stelis and related genera be truly characterized by the absence or very small amounts of heterochromatin? Therefore, we hope to contribute to a better understanding of the phylogeny of Pleurothallidinae and to identify the mechanisms involved in the karyotypic evolution of the subtribe. The subtribe Pleurothallidinae exhibits a wide diversity of chromosomal numbers and CMA/DAPI band patterns, potentially usable in the delimitation of taxa at the species and genus levels. The chromosomal numbers of species in the subtribe Pleurothallidinae ranged from 2n = 18 in a Pleurothallis species to 2n = 44 in Acianthera. Additionally, genera such as Acianthera and Specklinia were characterized by primary basic numbers x = 20 and x = 10, respectively, while for Stelis, the most probable primary basic number is x = 16. The quantity and distribution of CMA/DAPI bands varied clearly within the subtribe Pleurothallidinae and, in some cases, within the genera, such as in Acianthera and Stelis. Initially, the genus Stelis seemed to be characterized by having little or no detectable heterochromatin using the CMA and DAPI fluorochrome banding technique. However, Stelis showed more variability in terms of the quantity, composition, and number of heterochromatic bands, which are useful in the taxonomic delimitation of related species. Thus, we hope to contribute to a better understanding of the phylogeny of Pleurothallidinae.